Burundi : Staff Report for the 2014 Article IV Consultation, Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context: Since the last Article IV Consultation in 2012, notable progress has been achieved to enhance macroeconomic stability, underpinned by the Fund-supported program. However, continued progress could be tested as the country faces a more challenging environment, due to increasing social and political tensions and frequent strikes in the run-up to the 2015 elections. Moreover, recent political developments reinforce uncertainties surrounding external budget support. Program: The Executive Board approved the three-year arrangement under the Extended Credit Facility (ECF) on January 27, 2012, with a total access of SDR 30 million. The first, second, third, and fourth reviews were completed on July 27, 2012, February 14, 2013, September 6, 2013, and February 28, 2014, respectively. For the fifth review, all end-March performance criteria were observed, but fiscal revenues underperformed in the first quarter of 2014 requiring corrective fiscal measures (about 1 percent of GDP on an annual basis). Satisfactory progress has been made on structural reforms, albeit with some delays. Outlook and risks: The medium-term macroeconomic outlook is challenging. The principal near-term risk is an intensification of election-related uncertainty, economic disruptions and violence, which would affect investment and growth. Governance issues or delays in making measurable progress in public financial management (PFM) reforms, and heightening of political tensions could curtail donor support. Reintegrating repatriated refugees is likely to add to unemployment pressures, increase demand for public services, and exacerbate social conflict over access to land. Staff Views: The staff recommends the completion of the fifth review under the ECF arrangement, setting of revised performance criteria and indicative targets for September-December 2014, and disbursement of SDR 5 million. The authorities have consented to the publication of this report following the completion of the review.